A Novel Auditory Display for Neonatal Resuscitation: Laboratory Studies Simulating Pulse Oximetry in the First 10 Minutes After Birth. (February 2019) - Zestic, Jelena; Brecknell, Birgit; Liley, Helen; Sanderson, Penelope
Objective: We tested whether enhanced sonifications would improve participants' ability to judge the oxygen saturation levels (SpO2 ) of simulated neonates in the first 10 min after birth. Background: During the resuscitation of a newborn infant, clinicians must keep the neonate's SpO2 levels within the target range, however the boundaries for the target range change each minute during the first 10 min after birth. Resuscitation places significant demand on the clinician's visual attention, and the pulse oximeter's sonification could provide eyes-free monitoring. However, clinicians have difficulty judging SpO2 levels using the current sonification. Method: In two experiments, nonclinicians' ability to detect SpO2 range and direction—while performing continuous arithmetic problems—was tested with enhanced versus conventional sonifications. In Experiment 1, tremolo signaled when SpO2 had deviated below or above the target range. In Experiment 2, tremolo plus brightness signaled when SpO2 was above target range, and tremolo alone when SpO2 was below target range. Results: The tremolo sonification improved range identification accuracy over the conventional display (81% vs. 63%, p < .001). The tremolo plus brightness sonification further improved range identification accuracy over the conventional display (92% vs. 62%, p <.001). In both experiments, there was no difference across conditions in arithmetic task accuracy ( p >.05). Conclusion: Using the enhanced sonifications, participants identified SpO2 range more accurately despite a continuous distractor task. Application: An enhanced pulse oximetry sonification could help clinicians multitask more effectively during neonatal resuscitations.